Exploring the meaning of care among lived experiences of patients with blindness: an interpretive phenomenological study† - Mohammadi Mohammad Ali; Heidarzadeh Mehdi; Mehri Saeed; Shamshiri Mahmood (Sciendo, 2024)
To explore the meaning of care experienced by people with blindness in hospitals.